Implementasi Prinsip Perlindungan Perempuan Korban Kekerasan: Studi di UPTD PPA Sumatera Barat - A.Fernandos; Jendrius; Lucky Zamzami (Jurnal Sosiologi Nusantara, 2025)
Violence against women continues to be a significant issue that calls for decisive government action. In response, the Indonesian government established the Regional Technical Implementation Unit for the Protection of Women and Children (UPTD PPA) through PPPA Regulation Number 4 of 2018. The West Sumatra Provincial Government has formed UPTD PPA to provide protection services for women victims of violence. However, challenges remain in aligning the implementation of these services with the protection principles mandated in the national legal framework. This study aims to describe how the UPTD PPA of West Sumatra Province applies the principles of protection in handling cases of violence against women. Data were gathered using a qualitative descriptive approach through in-depth interviews, observations, and document analysis. The research informants consisted of five officers from the UPTD PPA of West Sumatra Province. Data were analyzed using the Miles and Huberman model, which involves data coding, data display, and conclusion drawing. The findings show that the implementation of the principles of non-discrimination and the best interests of the victim is nearly ideal. However, gender equality has not been fully realized. The principle of justice is fully aligned with the legal basis, while the principle of recovery is only partially so.